Culture of Corruption Politicians' Behavior in Parliament and State Official During Reform Government Indonesia (Genealogical Study) - Riyadi, Bambang Slamet; Wibowo, Basuki Rekso; Susanti, Vinita (International Journal of Criminology and Sociology, 2022)
This study aims to assess and analyze the Culture of Corruption Politicians' Behavior in Parliament and State Official During Reform Government Indonesia (Genealogical Study) This study is genealogical research based on the literature, journals and reporting publications of Indonesian corruption culture. The result of the study concluded that culture corruption behavior of politicians in the parliament and bureaucracy in the reform era in Indonesia is still ongoing corruption can be said as a culture of corruption that has been so severe, that Indonesia is almost categorized as a kleptocracy country, and as a country ruled by thieves (klepto) and even has been spread of viral infections or COVID-19.. This crime could even be called state organized crime in a corrupt government. This crime is based on the achievement of individual interests, groups or political parties and retains the power. The lack of success of Indonesian government in resolving the case of state officials or politicians involved in corruption, collusion and nepotism rapidly lightly court decisions, many cases delayed in its prosecution process, even termination of the case of important officials state to be an indication the weakness of law enforcement against white-collar criminals in Indonesia. This happens due to the severity of conflict of interest so the solution is often based on the interests or political bargaining and abuse of power.